Trends in Hospitalization and Incidence Rate for Syphilitic Uveitis in the United States From 1998 to 2009 - Albini, Thomas; Callaway, Natalia F.; Pershing, Suzann; Wang, Sean K.; Moshfeghi, Andrew A.; Moshfeghi, Darius M. (American journal of ophthalmology, 2017)
This study evaluates the annual incidence of syphilitic uveitis in the US and trends in hospital admissions over time. Retrospective, longitudinal incidence rate analysis of the National Inpatient Sample (NIS) data from 1998 to 2009. The NIS is a de-identified, random sample dataset of inpatient hospitalizations from 46 states. The number of cases of syphilitic uveitis was defined by (1) International Classification of Diseases, 9th Revision (ICD-9) code for syphilis and uveitis or (2) ICD-9 code for syphilitic uveitis. Annual case count, incidence rate, and trend over time were calculated. Multivariate logistic regression was used to evaluate associated factors for a syphilitic uveitis diagnosis. The study included 455 310 286 hospitalizations during a 12-year study period with a mean of 37 942 524 patients annually. Syphilis and uveitis was recorded for 1861 patients (155 annually) and syphilitic uveitis was diagnosed in 204 subjects (average of 17 cases annually). There was no change in the incidence of syphilitic uveitis, using either definition, over the study period (P for trend = .46). The mean annual incidence of syphilis and uveitis was 0.0004%, or 4 per million. Syphilitic uveitis had an annual incidence of 0.000045%, or 0.45 per million. The odds of syphilitic uveitis were lower among women (odds ratio [OR] 0.40, CI 0.28–0.57) and increased with comorbid acquired immunodeficiency syndrome (OR 4.52, CI 3.01–6.79). We report the first incidence of syphilitic uveitis in the United States. Fortunately, this remains a rare condition. The results demonstrate no change in the number of inpatient admissions for syphilitic uveitis during the study period.